Discursive delegitimisation of homosexuality on Chinese social media - Zhang, Ke; Zhuang, Huibin (Frontiers in Psychology, 2023)
This article contributes to the understanding of public representations of homosexuality in China by focusing on the case of a homophobic textbook. College student Xixi sued Jinan University Press (JUP) in 2017 for classifying homosexuality as a psychosexual disorder. Three years later, a Chinese court dismissed Xixi’s lawsuit against the allegedly homophobic textbook published by JUP. The ruling elicited responses on Chinese social media that demonstrated the polarisation of public opinion regarding homosexuality. This article investigates discursive representations of homosexuality in online space by analysing the public discourse surrounding this problem. Using van Leeuwen’s discursive delegitimation strategies (i.e., authorisation, moral evaluation, rationalisation, and mythopoesis), 496 comments posted on Sina Weibo were employed and subjected to discourse analysis. According to our findings, these strategies contribute to public opposition to homosexuality, portrayed as unhealthy, infertile, disruptive, and corrosive. The article concludes by discussing the emerging sociocultural factors on Sina Weibo that influence the anti-homosexuality attitudes of Weibo users.